Self-Control as a Mediator Between Financial Literacy and Saving Behavior in Generation Z - Irdawati; S, Reni Yesi; Rachmawati, Budi (Accounting Profession Journal (APAJI), 2025)
This study examines the determinants of saving behavior among Generation Z in Bekasi City, focusing on the influence of financial literacy and the mediating role of self-control. Using a quantitative approach, data were collected from 96 university students and analyzed through Structural Equation Modeling – Partial Least Squares (SEM-PLS). The findings reveal that financial literacy positively affects saving behavior both directly and indirectly via self-control, which partially mediates this relationship. Moreover, financial literacy significantly enhances self-control, and self-control itself strongly predicts saving behavior. These results underscore the importance of integrating behavioral components, such as self-control development, into financial education programs for young adults. The study contributes to a deeper understanding of how cognitive and psychological factors jointly influence financial decision-making in the digital age. Limitations include the cross-sectional design and limited geographic scope, suggesting future research to employ longitudinal methods and broader populations for generalizability.